Self-esteem and assertiveness in adolescents of secondary education of a state and private school of a sector of Santa Anita district - Ayvar Velásquez, Herlinda Griselda (2016)
The research aims to determine the relation between self-esteem and assertiveness in students from first to fourth grade from a public and a private high-school as well of a sector in Santa Anita district, province and department of Lima. The sample consisted of 220 students: 106 males and 114 females, between 11 to 15 years old, from first to fourth grade of high-school from both schools. Stanley Coopersmith Self-Esteem Inventory, school way, and the Assertive Conduct Self-report (ADCA-1) by García and Magaz were used as instruments. The present research was a descriptive, correlational design.The results shown a positive and significant relation between self-esteem and assertiveness in students from both schools.